2018
DOI: 10.1097/bpo.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Deep Venous Thrombosis Among Children With or Without Osteomyelitis

Abstract: Level II-prognostic, retrospective cohort comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…As a fatal disease caused by serious musculoskeletal infection, VTE needs to arouse the attention of clinical staff. It has been reported that children with OM may have increased susceptibility to VTE in previous epidemiologic studies [ 3 5 ]. Unfortunately, the transcriptional signatures between VTE and OM have not been intensively investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a fatal disease caused by serious musculoskeletal infection, VTE needs to arouse the attention of clinical staff. It has been reported that children with OM may have increased susceptibility to VTE in previous epidemiologic studies [ 3 5 ]. Unfortunately, the transcriptional signatures between VTE and OM have not been intensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This complication should always be considered in patients who present with a musculoskeletal infection, especially osteomyelitis (OM) in younger ones [ 1 , 2 ]. In recent years, the prevalence of DVT among acute haematogenous osteomyelitis (AHO) cases has been reported to be 6–10% [ 3 , 4 ]. In Taiwan, the risk of developing DVT was 2.49-fold in patients with chronic OM compared with the comparison cohort [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with osteomyelitis are at increased risk for developing DVTs and differ from those without DVT by higher severity of illness. 14,15 In pediatric patients, the presence of AHO, persistent bacteremia, especially with methicillin-resistant Staphylococcus aureus and respiratory findings are very suggestive of DVT. Screening for DVT in these patients is highly recommended, even in the absence of classic findings of DVTs.…”
Section: Discussionmentioning
confidence: 99%
“…Another specific pediatric orthopaedic population at increased risk of VTE is children with musculoskeletal infections such as osteomyelitis or septic arthritis, especially if the infecting organism is Staphylococcus aureus 9,19-23 . The severity and duration of elevation in C-reactive protein (CRP) may predict the development of VTE, with every 20 mg/L increase in peak CRP associated with a 29% increase in risk of thrombosis 24 .…”
Section: - Are the Risk Factors For Vte Following Orthopaedic Procedu...mentioning
confidence: 99%